Tibet-Guge: the cultural relics of ancient western Tibet - Beck, Michael (Vajra Books, 2018)
The Guge Kingdom (a Buddhist civilization rich with art and culture) was founded at the end of the 10th century. It flourished until its demise in the 17th century